Pulmonary Lymphangitis Carcinomatosa and Acute Pancreatitis: A Rare Presentation of Choledochal Cyst - Kelly, D. M. (Hindawi Publishing Corporation, 1999)
Pulmonary lymphangitis carcinomatosa is an unusal cause of death in a young adult. This case describes an apparently healthy young woman who presented with severe acute pancreatitis, which is a recognized complication of a choledochal cyst. Autopsy examination revealed advanced malignancy with poorly differentiated adenocarcinoma penetrating the wall of the choledochal cyst and metastatic adenocarcinoma in the lymph nodes, lungs and kidneys. This case emphasises the unusual presentation of a choledochal cyst with acute pancreatitis and the aggressive nature of malignancy associated with this congenital anomaly.